REALITAS FEMINISME DALAM KARYA LUKIS - Drs. Abd. Hafiz, M.Pd., Widya Mardiani, Drs. Erfahmi, M.Sn., (Jurusan Seni Rupa FBS UNP Padang, 2017)
The purpose of the creation of this final work is to remind people to more understand the line of both women and men. Especially for women to be more intelligent to sort out what things to do and what to leave behind. The method of creating this final paper uses five stages: preparatory phase, elaboration phase, synthesis phase, concept realization phase, and completion phase. The works that are visualized are about the reality of feminism. Among these works are: Boneka, Super Girl, Rindu, Y‟r not my Mother but Y‟r my Mom, Perjuangan, Salah Kaprah, Save Me, Adu Kekuatan, I Can do it, dan Kebutaan.Keywords : Reality, Feminism, Painting